Uma ferramenta para apoiar a pesquisa exploratória na Web - Campos, Thiago Prado (2013)
This work contextualizes the exploratory search; a kind of information seeking that has a focus on learning and investigative tasks. In this type of search, the researcher does not dominate the information space in which the problem is situated that, generally, is brought to it poorly structured. To drive the user to the success in conducting exploratory research, numerous specific support tools have been designed and created, with involvement of areas of HCI and Information Retrieval. These tools, however, have not yet reached the full coverage of the needs of the researchers involved in exploratory research tasks. One of these needs, for example, is a better support for activities of long and very-long term revisitation. As exploratory searches run multiple sessions and can overcome months of implementation, they need adequate support of the search history to provide support for the recall of important documents once visited. In this work, we identify the main dimensions that can enhance the success of an exploratory search, and proposed a tool to integrate the search history with these dimensions. This tool uses a visual approach to the presentation of the search history combined with factors of customization and organization of content, which is recorded during the research activities of the user. The results of a series of experiments indicated that most components inserted in the system were useful to the researchers and this is a reason for us to conclude that this is a promising way to support exploratory research.